IoT-Based Human Movement Monitoring System: Prospect for Conceptual Digital Twin - Parween, Gulfeshan; Al-Anbuky, Adnan; Mawston, Grant; Lowe, Andrew (ASME International, 2025)
The growing popularity of smart healthcare and novel innovations in human movement monitoring systems open doors for diagnosing various health conditions, including neurological disorders, musculoskeletal system problems, mobility limitations associated with aging, and the oversight of rehabilitation programs. This paper discusses the technical challenges, potential applications, and prospects for conceptual Digital Twin (DT) Technology in IoT-based human monitoring systems, underscoring its role in revolutionizing rehabilitation strategies. Current studies emphasize the possibilities of IoT and Digital Twin (DT) technologies across various sectors, including healthcare. However, given its use in real-time monitoring and follow-up of end-to-end rehabilitation programs is still emerging. Integrating Digital Twin in the existing IoT-based human movement monitoring system facilitates the handling of large amounts of data, supports analytics, and provides a platform for integrating additional services. This proposed framework incorporates inertia or wearable sensors to collect data on human activities during rehabilitation, utilizes fast Fourier transform (FFT) for feature extraction, and employs advanced Machine Learning algorithms for activity recognition along with Artificial Intelligence for predictive analytics. Furthermore, it implements a data-driven virtual model that mirrors physical behaviors for enhanced real-time monitoring and tunes the system based on personal requirements.
Keywords: 4605 Data Management and Data Science; 46 Information and Computing Sciences; Bioengineering; Aging; Machine Learning and Artificial Intelligence; Networking and Information Technology R&D (NITRD); Generic health relevance; 3 Good Health and Well Being